(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Diarrheal diseases remain one of the leading causes of morbidity and mortality among children under five years of age worldwide, particularly in low- and middle-income countries. Dehydration resulting from acute diarrhea is the primary factor contributing to severe complications and death in this age group. Oral rehydration solution (ORS) is recognized as a simple, effective, and cost-efficient intervention for the prevention and treatment of dehydration associated with diarrheal illnesses. The present article aims to analyze the significance of oral rehydration solution in the management of diarrhea in children under five years of age. The study highlights the mechanism of action of ORS, its clinical effectiveness, and its role in reducing hospitalization rates and mortality. Emphasis is placed on the importance of early administration of ORS and adherence to international treatment guidelines. The findings support the continued use of oral rehydration therapy as a cornerstone in the management of pediatric diarrheal diseases and underscore the need for increased awareness among healthcare providers and caregivers.